Plasminogen activator inhibitor-1 4G/5G polymorphism, factor V Leiden, prothrombin mutations and the risk of VTE recurrence - Sundquist, Kristina; Wang, Xiao; Svensson, Peter J.; Sundquist, Jan; Hedelius, Anna; Lönn, Sara Larsson; Zöller, Bengt; Memon, Ashfaque A. (Thrombosis and Haemostasis, 2015)
Plasminogen-activator inhibitor (PAI)-1 is an important inhibitor of the plasminogen/plasmin system. PAI-1 levels are influenced by the 4G/5G polymorphism in the PAI-1 promoter. We investigated the relationship between the PAI-1 polymorphism and VTE recurrence, and its possible modification by factor V Leiden (FVL) and prothrombin (PTM) mutations. Patients (n=1,069) from the Malmö Thrombophilia Study were followed from discontinuation of anticoagulant treatment until diagnosis of VTE recurrence or the end of the study (maximum follow-up 9.8 years). One hundred twenty-seven patients (11.9 %) had VTE recurrence. PAI-1 was genotyped by TaqMan PCR. Cox regression analysis adjusted for age, sex and acquired risk factors of VTE showed no evidence of an association between PAI-1 genotype and risk of VTE recurrence in the study population as a whole. However, by including an interaction term in the analysis we showed that FVL but not PTM modified the effect of PAI-1 genotype: patients with the 4G allele plus FVL had a higher risk of VTE recurrence [hazard ratio (HR) =2.3, 95 % confidence interval (CI) =1.5–3.3] compared to patients with the 4G allele but no FVL (reference group) or FVL irrespective of PAI-1 genotype (HR=1.8, 95 % CI=1.3–2.5). Compared to reference group, 5G allele irrespective of FVL was associated with lower risk of VTE recurrence only when compared with 4G allele together with FVL. In conclusion, FVL has a modifying effect on PAI-1 polymorphism in relation to risk of VTE recurrence. The role of PAI-1 polymorphism as a risk factor of recurrent VTE may be FVL dependent.
Keywords: Fibrinolysis; plasminogen; PAI-1 polymorphism; recurrence; venous thromboembolism